Physical Properties and Anti-Mosquito Activities of Lotion Male from Palm Flower Extract (Elaeis guineensis Jacq.) - M Arsita M Arsita; Uce Lestari; Elisma Elisma; M. R. Efendi M. R. Efendi (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Mosquitoes can carry protozoa, viruses, and worm larvae that can cause various diseases in humans.Mosquito repellent preparations that are widely sold in the market are in the form of lotion preparations.However, most formulas of mosquito repellent products on the market contain DEET (N, N-diethylmeta-toluamide) which has side effects such as symptoms of hypersensitivity, irritation, and urticaria.Male palm flower (Elaeis guineensis Jacq.) is a natural material that contains flavonoid and estragolecompounds that have activity as a mosquito repellent. Therefore, this study aimed to determinethe lotion activity of male palm flower extract (Elaeis guineensis Jacq.) as an insect repellent. Theprocedure steps in this study include sample preparation, extract making, and lotion formulation withextract concentrations of F1(1%), F2(2%), F3(3%), F4(4%), and F5(5%), evaluation of physicalproperties, test stability and test the protection power of the lotion against mosquitoes. The results ofthe physical properties test showed that the lotion preparation was in the appropriate range with thespecified parameters and was stable at room temperature storage. The results of the effectiveness testshowed that the most effective formula was the F5 which has the best physical properties and a verystrong protective power.